Jahresgaben des Museumsvereins - 1972 bis 1991 : Bestandskatalog. (Mönchengladbach : Städtisches Museum Abteiberg, 1992)
Albrecht, Jürgen ; Baumgarten, Lothar ; Becher, Bernd & Hilla ; Beuys, Jospeh ; Brecht, George ; Broodthaers, Marcel ; Buren, Daniel ; Byars, James Lee ; Campus, Peter ; Chia, Sandro ; Coenen, Otto ; Darboven, Hanne ; Dimitrijevic, Braco ; Droese, Felix ; Ettl, Georg ; Falk, Petra ; Filliou, Robert ; Fisher, Joel ; Hafner, Jonas ; Hartung, Georg ; Heerich, Erwin ; Hollein, Hans ; Katterbach, Ellen ; etc.
boek